Penyuluhan terkait Menurunkan Kecemasan pada Penderita Hipertensi dengan Terapi Komplementer Progressive Muscle Relaxation: Education regarding Reducing Anxiety in Hypertension Sufferers with Complementary Progressive Muscle Relaxation Therapy - Cahyono, Ibnu; Puspitasari, Yenny; Prasetyo, Joko; Indasah, Indasah (Jurnal Abdi Keperawatan dan Kedokteran, 2024)
Anxiety occurs when the condition of the body is disturbed due to psychological pressure which is a trigger for hormones in the body that control the mind of a person who is experiencing anxiety so that it can increase blood pressure. This community service aims to reduce the anxiety of Hypertension patients in the community by providing Progressive Muscle Relaxation education to the community. This community service activity will be carried out from May 3 to 5, 2024 in the work area of the Sematu Jaya Health Center with lectures, practices and discussion methods. with 10 participants. There was a decrease in anxiety, as many as 70.0% of community service participants did not experience anxiety after being given Progressive Muscle Relaxation. The way to find out how to reduce anxiety in hypertensive patients used in this community service activity is to ask and answer patients directly by interviewing using the Zung Self-Rating Axiety scale (SAS/SRAS) questionnaire instrument after being given Progressive Muscle Relaxation. The evaluation of the results obtained by participants understood and understood about hypertension, measuring blood pressure, and how to do Progressive Muscle Relaxation to reduce anxiety. Conclusion: Progressive Muscle Relaxation is effective in reducing anxiety in hypertensive patients.